Comparison of local infiltration and epidural analgesia for postoperative pain control in total knee arthroplasty and total hip arthroplasty: A systematic review and meta-analysis - Yan, Huan (Bosn J Basic Med Sci, 2016)
Pain management after total knee arthroplasty (TKA) and total hip arthroplasty should permit early mobilization with minimal pain. Local infiltration analgesia (LIA) is a new popular method for decreasing postoperative pain. The goal of this meta-analysis is to evaluate the efficacy of LIA in comparison with epidural analgesia. A literature search was performed in PubMed, EMBASE, the OVID database, Web of Science, and the Cochrane Library databases. The risk of bias was assessed using the Cochrane collaboration tool. Outcomes of interest included visual analog scale score, range of flexion, length of stay, and complications. Nine trials involving 537 patients met the inclusion criteria. LIA provides better pain relief and larger range of motion in TKA patients compared to epidural analgesia at the late postoperative period. No significant difference was observed in regard to the length of stay and complications. The current evidence shows that the use of local infiltration is effective for postoperative pain management in TKA patients. More high-quality randomized controlled trials with long-term follow-up are required for examining the long-term efficacy and safety of local infiltration.